The physicochemical fingerprint of Necator americanus - Chauhan, Veeren M.; Scurr, David J.; Christie, Thomas; Telford, Gary; Aylott, Jonathan W.; Pritchard, D.I. (Public Library of Science, 2017)
Necator americanus, a haematophagous hookworm parasite, infects ~10% of the world’s population and is considered to be a significant public health risk. Its lifecycle has distinct stages, permitting its successful transit from the skin via the lungs (L3) to the intestinal tract (L4 maturing to adult). It has been hypothesised that the L3 larval sheath, which is shed during percutaneous infection (exsheathment), diverts the immune system to allow successful infection and reinfection in endemic areas. However, the physicochemical properties of the L3 larval cuticle and sheath, which are in direct contact with the skin and its immune defences, are unknown. In the present study, we controlled exsheathment, to characterise the sheath and underlying cuticle surfaces in situ, using atomic force microscopy (AFM) and time-of-flight secondary ion mass spectrometry (ToF-SIMS). AFM revealed previously unseen surface area enhancing nano-annuli exclusive to the sheath surface and confirmed greater adhesion forces exist between cationic surfaces and the sheath, when compared to the emergent L3 cuticle. Furthermore, ToF-SIMS elucidated different chemistries between the surfaces of the cuticle and sheath which could be of biological significance. For example, the phosphatidylglycerol rich cuticle surface may support the onward migration of a lubricated infective stage, while the anionic and potentially immunologically active heparan sulphate rich deposited sheath could result in the diversion of immune defences to an inanimate antigenic nidus. We propose that our initial studies into the surface analysis of this hookworm provides a timely insight into the physicochemical properties of a globally important human pathogen at its infective stage and anticipate that the development and application of this analytical methodology will support translation of these findings into a biological context.